2015
DOI: 10.3389/fenrg.2015.00041
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of the Microalgae Cultivation Phase for Energy Production in Open Raceway Ponds and Flat Panel Photobioreactors

Abstract: A dynamic model of microalgae cultivation phase is presented in this work. Two cultivation technologies are taken into account: the open raceway pond and the flat panel photobioreactor. For each technology, the model is able to evaluate the microalgae areal and volumetric productivity and the energy production and consumption. Differently from the most common existing models in literature, which deal with a specific part of the overall cultivation process, the model presented here includes all physical and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…In Béchet et al (2018) a comparison of different evaporation models is presented. On the other hand, in Marsullo et al (2015), a dynamic model for the cultivation of microalgae is developed where an empirical temperature model based on thermal energy balances suggested in Slegers et al (2013) is included. These studies demonstrated the importance of temperature on microalgae growth and the complexity of accurately estimating its value.…”
Section: Introductionmentioning
confidence: 99%
“…In Béchet et al (2018) a comparison of different evaporation models is presented. On the other hand, in Marsullo et al (2015), a dynamic model for the cultivation of microalgae is developed where an empirical temperature model based on thermal energy balances suggested in Slegers et al (2013) is included. These studies demonstrated the importance of temperature on microalgae growth and the complexity of accurately estimating its value.…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study, a cylindrical PBR was preferred for scale‐up because of mixing and wall growth considerations (Lu et al, 2020). It has been suggested that the thickness of FPPBR should be limited to 5 cm to allow efficient light penetration (Adessi & De Philippis, 2014; Basak et al, 2014; Marsullo et al, 2015). However, a 10 cm‐thick, 10 L FPPBR was used for laboratory growth of PNSB (Lu et al, 2020) and FPPBR of 10 cm thickness (230 L volume) and 25 cm thickness (550 L volume) were used for long‐term outdoor operation (Gonzalez‐Camejo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to closed PBRs, surface-to-volume ratio and the corresponding light penetration in open ponds system are far from ideal; although direct sunlight is too strong for most microalgae, most of them only need 1/10 of direct sunlight [88]. Mainly, in most open pond system, only the top 7–10 cm of water are exposed to enough light penetration for efficient photosynthesis [89], the causes are bulk algal biomass that is accumulated in the surface which leads to blocking natural light sources and preventing it from reaching deeper into the water [90]. However, one main advantage of open culture systems is that they are inexpensive to install and operate [87].…”
Section: Approaches To Promote Lipids Productionmentioning
confidence: 99%